Giardiasis as a neglected disease in Brazil: Systematic review of 20 years of publications - Coelho, Camila Henriques; Durigan, Maurício; Leal, Diego Averaldo Guiguet; Schneider, Adriano de Bernardi; Franco, Regina Maura Bueno; Singer, Steven M. (PLOS Neglected Tropical Diseases, 2017)
Author summary Giardiasis is an intestinal disease that affect millions of people worldwide, including children. Its main route of transmission is by ingestion of food or water contaminated with the protozoan G. duodenalis. Transmission does not require an animal host, although transmission from animals to human (zoonotic transmission) has been confirmed as an important vector of human giardiasis. This study is a comprehensive description of the impact of giardiasis in Brazil based on studies published in the country from the past 20 years. We describe Giardia prevalence in humans (including indigenous populations), animals and water supplies. In addition, we create a transmission network model for the disease, based on genotype data previously identified in animal and human hosts as well as in environmental samples. The data compiled here will be useful for design of policies to prevent giardiasis transmission in Brazil.